Ramy prawne przesłuchania świadka na posiedzeniu zdalnym w postępowaniu cywilnym - Misztal-Konecka, Joanna (PRAWO i WIĘŹ, 2025)
The introduction of remote hearings in civil proceedings has opened up new possibilities for presenting evidence, including witness testimony. While the legislator has granted the presiding judge and the witness the right to initiate a remote hearing, the final decision lies with the parties, who can raise a binding objection to the remote examination of a witness. While remote witness examination has several advantages, such as saving time and resources, offering organisational benefits and speeding up proceedings, it also carries certain risks, including technical difficulties, the possibility of influencing the content of testimony and violating personal data protection. The article highlights the above advantages and disadvantages of remote witness examination and notes the legislative shortcomings that need to be addressed.